Reformasi Sektor Keamanan Demi Demokrasi Penanganan Terorisme di Indonesia - Perwita, Anak Agung Banyu (Jurnal Ilmu Sosial dan Ilmu Politik, 2005)
Security Sector Reform (SSR) has been takes place in Indonesia. It requires strategic participation of civil society actors, particularly in helping to manage and oversight the security sector. In this regard, SSR essentially is a process of the civilianisation of security sector bureaucracies and the de-politicisation of the security sector, or process of establishing appropriate structures for (democratic) civilian control. Given terroris is a threat to security and in Indonesia, this article also attempts to link the importance of SSR with enhancing capacity for combating terrorism terrorism. It identifies lessons that civilians and military in Indonesia can learn from.